Molecular underpinnings of induced degenerative heterogeneity in the retinal pigment epithelium - Krishna Kumar Singh; Yang Jin; Ming-Wen Hu; Isabella Palazzo; Marisol Cano; Thanh Hoang; Imran Bhutto; Shusheng Wang; Debasish Sinha; Seth Blackshaw; Jiang Qian; James T. Handa (Proceedings of the National Academy of Sciences, 2026)
Cigarette smoking induces epigenetic changes that can cause degenerative heterogeneity with aging and disease. In disease such as age-related macular degeneration (AMD), the leading worldwide cause of blindness among the elderly, retinal pigment epithelial (RPE) cell heterogeneity is a key change. Since smoking is a powerful risk factor for AMD, we hypothesized that smoke induces epigenetic-mediated degenerative RPE heterogeneity. We administered cigarette smoke condensate (CSC) to young and aged mice. Using snRNA-seq and single nuclear ATAC sequencing, we identified distinct healthy and dedifferentiated RPE clusters in both aged vehicle- and young CSC-treated mice. Dedifferentiated RPE had globally decreased chromatin accessibility and expression of genes linked to “hallmarks of aging.” Notably, young, dedifferentiated RPE also exhibited a compensatory upregulation of hallmarks of aging-related genes including mitochondrial function and proteostasis while aged dedifferentiated RPE did not, which decreased their survival following CSC treatment, as experimentally verified with TUNEL labeling. Similar populations of dedifferentiated and healthy RPE were identified both in mice exposed to cigarette smoke for 4 mo and in macular RPE from a donor who smoked and another with early AMD, but not from a nonsmoker donor. Degenerative cellular heterogeneity that includes an abnormal cluster can jeopardize cell survival and represents a hallmark of ocular aging.